Reviewing the taxonomy of Podaxis: Opportunities for understanding extreme fungal lifestyles. Issue 3 (March 2019) - Conlon, Benjamin H.; Aanen, Duur K.; Beemelmanns, Christine; de Beer, Z. Wilhelm; De Fine Licht, Henrik H.; Gunde-Cimerman, Nina; Schiøtt, Morten; Poulsen, Michael
Abstract: There are few environments more hostile and species-poor than deserts and the mounds of Nasutitermitinae termites. However, despite the very different adaptations required to survive in such extreme and different environments, the fungal genus Podaxis is capable of surviving in both: where few other fungi are reported to grow. Despite their prominence in the landscape and their frequent documentation by early explorers, there has been relatively little research into the genus. Originally described by Linnaeus in 1771, in the early 20th Century, the then ∼25 species of Podaxis were almost entirely reduced into one species: Podaxis pistillaris . Since this reduction, several new species of Podaxis have been described but without consideration of older descriptions. This has resulted in 44 recognised species names in Index Fungorum but the vast majority of studies and fungarium specimens still refer to P .  pistillaris . Studies of Podaxis ' extremely different lifestyles is hampered by its effective reduction to a single-species genus. Here we examine the history of the taxonomy of Podaxis before focusing on its extreme lifestyles. From this, we consider how the muddled taxonomy of Podaxis may be resolved; opening up further avenues for future research into this enigmatic fungal genus. Highlights: Podaxis survives in both hot deserts and the interior of termite mounds. Many herbarium specimens apparently mislabeled as a single species. Podaxis possesses adaptations to desert life and grows at high temperatures. Podaxis produces a broad range of secondary compounds. The genus has great potential for further study.